2003
DOI: 10.1046/j.1445-2197.2003.t01-1-02651.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of emergency common bile duct exploration: impact of preoperative endoscopic decompression

Abstract: Among patients requiring emergency CBDE, uncomplicated preoperative endoscopic biliary decompression benefits patients with acute cholangitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It has been speculated that acute cholangitis can lead to high morbidity from postoperative complications, as well as mortality. [13][14][15] Thus, we inferred a relationship between hepatolithiasis surgery and pathogenesis through the following route: preoperative attack of acute cholangitis/intraoperative hemobilia/postoperative complications. In addition to ISAC, we found that the preoperative severity of acute latest cholangitis was associated with intraoperative hemobilia.…”
Section: Commentsmentioning
confidence: 99%
“…It has been speculated that acute cholangitis can lead to high morbidity from postoperative complications, as well as mortality. [13][14][15] Thus, we inferred a relationship between hepatolithiasis surgery and pathogenesis through the following route: preoperative attack of acute cholangitis/intraoperative hemobilia/postoperative complications. In addition to ISAC, we found that the preoperative severity of acute latest cholangitis was associated with intraoperative hemobilia.…”
Section: Commentsmentioning
confidence: 99%
“…Performing a laparoscopic cholecystectomy with intraoperative cholangiogram which can be potentially converted to a CBD exploration in the background of underlying sepsis would be considered high risk in this subgroup of patients. 20 With respect to gallstone-related indications where inpatient MRCP confirmed choledocholithiasis, almost half of these patients proceeded to an inpatient ERCP. Indications for discharge prior to therapeutic intervention may be related to clinical or biochemical improvement and the availability of inpatient ERCP.…”
Section: Cholelithiasis and Managementmentioning
confidence: 99%